Extra Virgin Olive Oil Quality, Safety, and Authenticity - Varzakas, Theodoros (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The prevention and bioactivity effects associated with the so-called "Mediterranean diet" make olive oil the most consumed edible fat in the food intake of the Mediterranean basin.The road to quality demands that legislation should be followed. Hence, official European Union classifications such as protected designation of origin (PDO), protected geographical indication (PGI), etc. guarantee the quality and the origin of the labeled foodstuff.The profiling of volatile components and the aroma of olive oil are key factors in the quality dimension and are affected by various factors and conditions such as cultivar; atmospheric, pedologic, and fostering conditions; the ripening degree; olive and oil storage; and the technology of oil extraction from drupes, as well as the quality of the pre-extraction procedures.In extra virgin olive oil production, as in all kinds of production, the maintenance of high quality standards is assured by the olive fruits' and the final products' quality. Modern milling technologies can aid in the direction of quality and safety and thus can be employed in the production of extra virgin olive oil (EVOO), which can be directly consumed without any further manipulation. The overall quality of EVOO should be determined by quality characteristics including sensory analysis, stability, and nutritional value and safety (microbiology, absence of contaminants and toxins), along with authenticity.Food authenticity issues are very important for the food industry due to legislation aspects, economics, quality specifications and conformance, safety concerns, and religious matters. Authentic EVOO should comply with the producer's declaration regarding the quality of olive fruits, natural components, the absence of extraneous substances, production technology, the geographical and botanical origin, the production year, and the genetic identity. Hence, olive oil authenticity can be implemented by the validation of the application of accurate specifications for olive fruits and the selection of trustworthy suppliers with a quality assurance system in place. Authenticity methodologies will avoid adulteration but will also aid the control of accidental contaminations, e.g., in factories, where several oils are produced or used at the same time, or cross-contaminations.